Pemberdayaan Pembudidaya Ikan di Desa Bukit Bamba melalui Pelatihan Pembuatan “Pahesang” Pakan Herbal Daun Sangkareho (Callicarpa longifolia Lam.): Dissemination Fish Farmers in Bukit Bamba Village through Training on Making "Pahesang" Herbal Feed from Sangkareho Leaves (Callicarpa longifolia Lam.) - Maryani, Maryani; Rozik, Mohamad; Handayani, Tutwuri; Rosdiana, Rosdiana; Nursiah, Nursiah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
In freshwater fish cultivation, information and technology on alternative feed, namely feed mixed with herbs, has developed rapidly, one of which is artificial herbal feed from the medicinal plant Sangkareho (Callicarpa longifolia Lam.). This medicinal plant is a typical plant of Central Kalimantan. The aim of implementing this activity is to increase the knowledge and skills of partners or the fish-cultivating community regarding techniques for making herbal feed for fish cultivation with nutritional content formulations that suit the needs of cultivated fish. This activity will be carried out in Bukit Bamba Village, Central Kahayan District, Pulang Pisau Regency, Central Kalimantan with the target partners being fish farmers in Bukit Bamba Village. The method used to achieve this goal is active participatory empowerment of the community through collaboration with partners, namely the transfer of knowledge and technology through training activities on techniques for making herbal feed for cultivating fish in the form of pellets using local forest products, namely Sangkareho leaves, through direct assistance in the field starting from the process of taking and selecting raw materials to the production of herbal feed.